DESIGN STRUCTURE GREEN BUILDING ANTAPURA HOTEL IN KUNINGAN REGENCY - Nurpadilah, Radi (Journal of Business Social and Technology, 2025)
Kuningan Regency is one area that is considered to have tourism potential with mountainous geographical conditions with various natural beauty and natural springs In order to get the best outcomes, Kuningan Regency needs competent and well-planned management. Kuningan Regency's commercially managed hotel, which offers lodging and service services to the local population, is one of the facilities that supports tourism. It is anticipated that the hotel's presence will blend in with the surrounding area and complement the location of the establishment. Kuningan's need for hotel services will rise in proportion to the number of visitors. Building a hotel in Manis Kidul, Jalaksana District, Kuningan Regency, West Java, is proposed in response to the growing demand for hotel accommodations. Collect primary and secondary data and then conduct pre-eliminary design,design and structure analysis used Etabs v19 application. Green construction, green building, and sustainable building are other names for green building. A concept called sustainable building is offered as a solution to issues like global warming and natural disaster damage. A «green building» is one that is constructed using sustainable materials, energy efficiency, and ecologically friendly design principles. As per the Green Building Council Indonesia, a green building is one that incorporates sustainable practices in its planning, construction, operation, and maintenance elements, hence conserving natural resources, preserving the building's quality, and safeguarding the environment. Natural resources, preserving the standard of indoor air quality and building quality, Its focus on the well-being of its residents, all of which are grounded in the ideas of sustainable development. From the design of the planning of Green Building Antapura Hotel in Kuningan Regency using reinforced concrete structures, obtained each dimension of the structure. Considering the budget plan's computation for Green Building Antapura Hotel , it is estimated that it will cost Rp 29.227.700.000.00.